Endoscopic transoral nasopharyngectomy. Issue 1 (30th September 2020) - Soriano, Roberto M.; Rindler, Rima S.; Helman, Samuel N.; Pradilla, Gustavo; Solares, C. Arturo
Abstract: Background: A minimal access technique for the management of nasopharyngeal tumors extending below the palatal plane and laterally beyond the pterygoid musculature is yet to be developed. In this study we demonstrate the feasibility of endoscopic transoral nasopharyngectomy (ETON) for resection of large nasopharyngeal lesions as a natural orifice alternative to traditional approaches. Methods: ETON was completed in three latex‐injected specimens. Surgical freedom (SF) and angles of attack (AoA) were calculated along the internal carotid artery (ICA). Results: An endoscopic transoral approach was successfully used to identify the parapharyngeal ICA and subsequently perform a complete nasopharyngeal resection. SF and AoA (sagittal) were found to be the greatest at the anterior genu of the ICA. Conclusions: ETON is feasible. It provides wide exposure of the skull base and proximal control of the ICA. It may be indicated for the management of nasopharyngeal tumors with inferolateral extension, involving the ICA.